1202. Subinhibitory Concentrations of Omadacycline Inhibit Staphylococcus aureus Hemolytic Activity in Vitro. (31st December 2020) - Serio, Alisa W; Tanaka, S Ken; Wright, Kelly; Garrity-Ryan, Lynne
Abstract: Background: In animal models of Staphylococcus aureus infection, α-hemolysin has been shown to be a key virulence factor. Treatment of S. aureus with subinhibitory levels of protein synthesis inhibitors can decrease α-hemolysin expression. Omadacycline, a novel aminomethylcycline antibiotic in the tetracycline class of bacterial protein biosynthesis inhibitors, is approved in the United States for treatment of community-acquired bacterial pneumonia (CABP) and acute bacterial skin and skin structure infections (ABSSSI) in adults. This study was performed to determine the durability of inhibition and effect of subinhibitory concentrations of omadacycline on S. aureus hemolytic activity. Methods: All experiments used the methicillin-sensitive S. aureus strain Wood 46 (ATCC 10832), a laboratory strain known to secrete high levels of α-hemolysin. Minimum inhibitory concentrations (MICs) of omadacycline and comparator antibiotics (tetracycline, cephalothin, clindamycin, vancomycin, linezolid) were determined. Growth of S. aureus with all antibiotics was determined and the percentage of hemolysis assayed. "Washout" experiments were performed with omadacycline only. Results: S. aureus cultures treated with 1/2 or 1/4 the MIC of omadacycline for 4 hours showed hemolysis units/10 8 CFU of 47% and 59% of vehicle-treated cultures, respectively (Fig. 1A, 1B ). In washout experiments, treatment with as little as 1/4 the MIC of omadacycline for 1 hour decreased the hemolysis units/10 8 CFU by 60% for 4 hours following removal of the drug (Table 1 ). Figure 1 Table 1 Conclusion: Omadacycline inhibited S. aureus hemolytic activity in vitro at subinhibitory concentrations and inhibition was maintained for ≥ 4 hours after removal of extracellular drug (Fig. 2 ). The suppression of virulence factors throughout the approved omadacycline dosing interval, in addition to the in vitro potency of omadacycline, may contribute to the efficacy of omadacycline for ABSSSI and CABP due to virulent S. aureus . This finding may apply to other organisms and other virulence factors that require new protein synthesis to establish disease. Figure 2 Disclosures: Alisa W. Serio, PhD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) S. Ken Tanaka, PhD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Kelly Wright, PharmD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder) Lynne Garrity-Ryan, PhD, Paratek Pharmaceuticals, Inc. (Employee, Shareholder)